INDIRECT REQUESTS BY THE EMPLOYERS IN THE HELP MOVIE - Wiruma Titian Adi; Madyantini Febrianti (Center of Language and Cultural Studies [CLCS], 2016)
This research aims to describe the use of indirect request in women’s language. This research used qualitative method and library research. Data were collected using grounded theories of indirect request for referents. The researcher put the theory of Indirect Requests into a movie because there would be so many conditions in the movie which can be explored by the theory. Besides, whether this theory is really being conscious or not by the masses, it is always used in daily conversation. The result of this research indicated that requests have intended meanings that are different from their literal meanings, and hearers recognize their real meaning based on the context. Using indirect request the speaker wants to be understood and the addressee wants to understand.